Analysis of the Effect of Shear Walls on Building Structural Deviations in High-rise Buildings Monde City Tower M2 Batam City - Fernando Fernando; Ade Jaya Saputra (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2022)
High-rise buildings are structures that are prone to lateral loads. Every high-rise building design requires a strong structure to withstand lateral loads due to earthquake and wind loads. The use of Shear Walls can reduce the displacement that occurs due to lateral loads received because of earthquake loads and wind loads. This study aims to analyze the effect of Shear Walls on the Monde City Tower M2 Apartment building in Batam City. The method used in this study is a numerical analysis in the form of modeling a 15-story apartment building located in Batam City. The building is modeled into 2 types, namely (V1) a structure without using Shear Walls and (V2) a structure using Shear Walls according to the structural drawings. The earthquake analysis was carried out using the response spectrum method with the software ETABS v 18.1.0 for the structural analysis calculations. The results of the analysis obtained in the form of the deviation value from a structure that uses shear wall have decreased the deviation in the X direction by 12.5476 % and a decrease in the deviation in the Y direction by 68.1254 %. P-Delta in a structure that uses a shear wall is much better in structural stability than a structure that only uses a frame system.